Analisis Faktor Risiko Nyeri Punggung Bawah Pengemudi Ojek Online Motor di Kota Makassar - Batutah, Syaiq Ibnu; Mulyadi; Stientje (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2023)
Low back pain or low back pain (LBP) is a musculoskeletal disorder resulting from an inappropriate body position when working or doing activities. Low back pain is a very common health problem worldwide and a leading cause of disability affecting work and general well-being. Complaints of low back pain can occur in everyone, both gender, age, race, educational status and profession. This study aims to determine the risk factors for years of service, length of work, and age with complaints of lower back pain among online motorcycle taxi drivers in the city of Makassar. This research is an analytic research with a cross-sectional research design, a total sample of 73 people from a total population of 90 people and data analysis was tested with a statistical person correlation test. From the research that has been done, the results of the three variables studied are years of service (p = 0.031), length of work (p = 0.048), and age (p = 0.355). The results showed that the length of work variable had a significant relationship with complaints of low back pain where the value was (p = 0.031 ˂ α = 0.05), as well as the length of work had a significant relationship with complaints of low back pain where the value was (p = 0.048 ˂ α = 0.05), while the age variable did not have a significant relationship with complaints of low back pain where the value was (p = 0.355 ˃ α = 0.05). The conclusion from this study is that the variables of length of work and years of service have a relationship with back pain while the age variable has no relationship with back pain for online motorcycle taxi drivers.Keywords : low back pain, online motorcycle taxi drivers